THE INFLUENCE OF THE EFFECTIVENESS OF ACUPRESSURE THERAPY ADOLESCENT GIRLS - Sakina, Nur Higma; Sahrudi, Sahrudi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Based on data from the World Health Organization (WHO) in 2020, the incidence of dysmenorrhoea was 1769,425 (90%) women suffering from dysmenorrhoea, with 10-16% suffering from severe dysmenorrhoea. The incidence of dysmenorrhea in the world is very high. On average, more than 50% of women suffer from it (Herawati, 2021). Dysmenorrhea is one of the many gynecological problems, which affects most women and if left untreated causes the inability to carry out activities every month. Research Objectives: This study aims to determine the effect of the effectiveness of acupressure therapy on dysmenorrhea in adolescent girls at Karya Bangsa Vocational School, Tangerang City. Research Method: This research is a pre-experimental quantitative research which aims to determine the effect of acupressure therapy at the switch point on dysmenorrhea pain in teenage female students at Karya Bangsa Vocational School, Tangerang City. The sample size used in this research was based on the type of experimental research. In this research, the sample size used was 38 respondents. This research uses a formula according to (Arikunto, 2014) Research Results: Based on the results of the Wilcoxone Signed Ranks Test statistical test on pain levels, significant results were obtained, p value = 0.000 < 0.05. The results of this analysis show that acupressure therapy has an effect on reducing the dysmenorrhea pain scale. Conclusions and Suggestions: There is an effect of providing acupressure therapy on dysmenorrhea in young women at Karya Bangsa Vocational School, Tangerang City. It is hoped that it can develop seminar and training programs on non-pharmacological therapy, especially acupressure for nurses or other health workers.